1987
DOI: 10.1128/jb.169.6.2691-2696.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of elastase genes from Pseudomonas aeruginosa

Abstract: A gene bank was constructed from Pseudomonas aeruginosa PAO1 and used to complement three P. aeruginosa elastase-deficient strains. One clone, pRF1, contained a gene which restored elastase production in two P. aeruginosa isolates deficient in elastase production (PA-E15 and PAO-E105). This gene also encoded production of elastase antigen and activity in Escherichia coli and is the structural gene for Pseudomonas elastase. A second clone, pHN13, contained a 20-kilobase (kb) EcoRI insert which was not related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 40 publications
1
55
1
Order By: Relevance
“…lasB-mediated elastolytic activity was determined by the elastin-Congo red (ECR) assay as described previously (35). Uninoculated TSB was included as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…lasB-mediated elastolytic activity was determined by the elastin-Congo red (ECR) assay as described previously (35). Uninoculated TSB was included as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…P. aeruginosa elastase was kindly supplied by Dr. Barbara Iglewski (Rochester, New York) and also purchased from Nagase and Company, Ltd., Tokyo, Japan. These preparations were homogeneous as demonstrated by SDS-PAGE and functionally active as demonstrated by digestion of Hide powder azure according to previously published methods (29). There was <1 pg/ mL of LPS in these preparations as demonstrated by limulus amebocyte lysate assay (Associates of Cape Cod., Inc.).…”
mentioning
confidence: 99%
“…A third possibility is that the 8-kb fragments have a normal promoter and some unknown factor(s) may play a role for regulating elastase gene expression in these non-elastase-producing Pseudomonas strains. Schad and coworkers (25) suggested that more than one gene is involved in elastase production in P. aeruginosa strains. To resolve these issues, it is necessary to clarify the promoter region for elastase.…”
Section: Discussionmentioning
confidence: 99%
“…Several elastase-related products (8,9,21), the existence of "pro" protein (2,6,9,29), and elastase activation molecules (9,26) have been described. In addition, Goldberg and Ohman (8) and Schad et al (25) first cloned the elastase-related lasA gene, which was later determined to be an elastase-modifying gene (9,26). However, the regulatory mechanism of elastase production has not yet been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation